Case report: Primary pleural giant extraskeletal Ewing sarcoma in a child - Wu, Yang; Xie, Chao-Bang; Huang, Qiong; Zhao, Kai-Fei (Frontiers in Oncology, 2023)
Primary extraskeletal Ewing sarcoma (EES) is a rare small round cell malignancy that accounts for less than 1% of all sarcomas. It is found most commonly in the trunk and lower limbs, and very rarely in the pleura and can be easily misdiagnosed in clinical practice. This study presents the case of a 11-year-old boy who presented to our hospital with no apparent cause of left shoulder pain for 6 months. On physical examination, tenderness was noted in the left chest wall and shoulder joint, which had limited range of motion. Computed tomography (CT) and magnetic resonance imaging (MRI) of the chest revealed an irregular soft tissue mass in the upper left thorax, with a wide base attached to the adjacent pleura and bone destruction of the adjacent left first rib. The patient’s bone scan showed a dense focus of increased radiotracer accumulation in the left first rib. A subsequent CT-guided aspiration biopsy of the left pleural mass with histomorphology and immunohistochemical phenotyping led to a diagnosis of extraskeletal Ewing sarcoma. To inhibit tumor growth, alternating systemic chemotherapy cycles of vincristine, doxorubicin, and cyclophosphamide (VDC) and isocyclophosphamide and etoposide (IE) were administered at 3-week intervals. After completing three VDC and two IE cycles, the child’s condition was well and the pain in the left shoulder joint was relieved. However, a repeat MRI of the chest showed that the mass did not shrink.